Biological decomposition of fulvic acid preparations - Kunc, F; Lokhmacheva, R A; Macura, J (Folia microbiologica, 1976)
Decomposition of preparations of various fractions of fulvic acids in pure cultures of bacteria and in the soil was investigated. In the soils enriched with fulvic acids the amount of bacteria increased, oxygen consumption and formation of carbon dioxide followed a typical sigmoid curve. The above measurements indicated that mineralization occurred after a very short or negligible lag phase. During the decomposition of fulvic acids the ability of microorganisms to oxidize aromatic compounds, e.g. vanillic and p-hydroxybenzoic acid, increased. The presence of aromatic structures in the used preparations of fulvic acids was demonstrated on the basis of their IR spectra and according to the results of chromatographic analyses of their hydrolysates. The results indicated a relationship between metabolism of fulvic acids and aromatic compounds. In samples of the soil preincubated with glucose with fulvic acids decomposed more rapidly than in untreated samples.
Keywords: Bacteria; benzopyrany; hydroxybenzoáty; spotřeba kyslíku; Benzopyrans; půdní mikrobiologie; Hydroxybenzoates; Carbon Dioxide; oxid uhličitý; Vanillic Acid; Biodegradation, Environmental; Soil Microbiology; biodegradace; kyselina vanilová; Oxygen Consumption